Experimental research on frictional resistance of smart isolation tool during maintenance operation in offshore pipeline. Issue 7 (3rd August 2018) - Zhang, Kang; Zhu, Xiaoxiao; Zhang, Shimin; Ding, Qingxin; He, Zichen
Abstract : Purpose: Pipeline maintenance technology using smart isolation tool is becoming more widely used in the global scope. This paper aims to investigate the effects of parameters on the frictional resistance between the slip and pipeline and the frictional characteristics under different lubrication films. Design/methodology/approach: An experimental platform consisting of slip, pipeline and data acquisition system was developed, wherein the slip slips on the pipeline under different normal forces and velocities. In addition, three lubrication conditions, namely, dry wall, oil liquid and black powder on the wall, were investigated to study the effects of lubrications on the frictional coefficient and characteristics. Findings: Research results indicate that the frictional force and coefficient were sensitive to normal force. The crude oil affected the frictional coefficient within a certain range of normal force, and the black powder enhanced the surface roughness in the natural gas pipeline. However, velocity had no effect on them. In addition, different contact behaviors could be observed from the frictional coefficient curves. Originality/value: In this paper, the effects of normal force and velocity on frictional resistance of sliding slip during decelerating process in pipeline were investigated, and the effects of lubrication films on frictional characteristics were also revealed. The research results are of great value to improve the prediction accuracy of smart isolation tool, and also provide a guiding significance for the development of maintenance operation in pipelines.